PENERAPAN METODE BERMAIN PERAN DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA 5-6 TAHUN DI TK KARTIKA 1-4 PEKANBARU - Henik Srihayati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Background this study is the most difficult children tell in their own words about the practice or an event that happened, for example when they told me about their experiences. Their most difficult child listening to the teacher. The purpose of this research is to improve the language skills of children aged 5-6 years. This research is a classroom action research on language skills (speaking and listening) the method of playing the role of children in TK Kartika 1-4 Pekanbaru. The results of this research note that the language skills of children which consists of speaking and listening skills has increased in each cycle. This is supported by: (1) initial score on the aspect of speaking proficiency by 55, while the listening skills of 53.9; (2) in the first cycle 1 meeting speaking ability 64.4. At the meeting of 2 speech at 75. The ability to listen to the meeting 1 for 60. At the second meeting amounted to 68.9; (3) the second cycle of meetings 1 speech at 82.8. At the second meeting of 90.6. The ability to listen to the first meeting of 82.8. At the second meeting of 90.6. The implication of this research is the teachers should inculcate the concept of activity implementation methods play a role to improve the language skills of children. This is done so inspires something that exists within the child so that the child's proficiency in speaking and listening can be achieved with good.